Spin and wavelength multiplexed nonlinear metasurface holography - Weimin Ye (Nature Portfolio, 2016)
Metasurfaces offer an approach for computer generated holograms with good efficiency and ease of fabrication. Here, Ye et al.report on spin and wavelength multiplexed nonlinear metasurface holography, showing construction of holographic images using fundamental and harmonic generation waves of different spins.